COVID-19 and Mortality, Depression, and Suicide in the Polish Population - Rogalska, Anna; Syrkiewicz-Świtała, Magdalena (Frontiers in Public Health, 2022)
Aim: The study was aimed at assessing the mortality of the population, the occurrence of the phenomenon of depression and suicide before and during the COVID-19 pandemic. Methods: Data on total mortality in Poland in 2017-2021 came from the report of the Ministry of Health. Data on the number of sick leave due to mental disorders were taken from the report of the ZUS (Social Insurance Institution in Poland). Data on the number of suicides came from police statistics. Results: Increase in the number of deaths in Poland in 2021 compared to the 2017-2019 average - 26.86%. In 2018-2020, the greatest number of fatal suicides was recorded in the age group - 60-64 years (in 2018 N = 565; 10.90%; in 2020 N = 524; 10.15%). Conclusions: In the years 2020-2021, an increase in mortality was observed in Poland compared to the previous years. Moreover, in 2020 there was an increase in sickness absence due to ICD-10 F.32 and an increase in the number of suicide attempts.